IDENTIFIKASI SIFAT KIMIA TANAH ULTISOL LAHAN KELAPA SAWIT DI DESA KELOMPU KECAMATAN KEMBAYAN KABUPATEN SANGGAU - Agustine, Leony; Sulakhudin, Sulakhudin; Anindita, Marta (Agros Journal of Agriculture Science, 2024)
Oil palm plantations managed by farmers in Kelompu Village, which is located on Ultisol land, are facing a decline in production due to low nutrient availability. The main limiting factor affecting soil productivity is the low availability of nutrients in the soil. One of the soil properties that greatly determines nutrient availability and plant productivity is the chemical characteristics of the soil. The research aims to study the chemical properties of soil on smallholder oil palm plantations in Kelompu Village. The research was conducted in Kelompu Village, Kembayan District, Sanggau Regency, with an area of around 20 hectares. There are four types of land based on farmer ownership and management. The survey and soil sampling method uses a grid system method. Soil samples were taken at a depth of 0-30 cm and 30-60 cm in a composite manner for analysis of soil chemical properties. Whole soil samples were also taken using a ring sampler at a depth of 0-30 cm. Soil analysis in the laboratory includes measuring soil pH, organic C content, total N, available P, K-dd, soil cation exchange capacity, soil base saturation and bulk density. Oil palm fields in Ultisol soil at all locations have similar soil chemical characteristics, with a tendency to have low nutrient levels. This was proven through analysis of soil samples which showed low levels of essential nutrient elements. In addition, limited management and land management practices, such as unbalanced fertilization, impact soil chemical properties and the availability of nutrients in the soil.Keywords: Ultisol Soil, Chemical Properties, Palm Oil INTISARIPerkebunan kelapa sawit yang dikelola oleh petani di Desa Kelompu, yang berada di tanah Ultisol, menghadapi penurunan produksi akibat rendahnya ketersediaan unsur hara. Faktor pembatas utama yang mempengaruhi produktivitas tanah adalah rendahnya ketersediaan hara di dalam tanah. Satu di antara sifat tanah yang sangat menentukan ketersediaan hara dan produktivitas tanaman adalah karakteristik kimia tanah. Penelitian bertujuan untuk mempelajari sifat kimia tanah pada lahan perkebunan kelapa sawit rakyat di Desa Kelompu. Penelitian dilakukan di Desa Kelompu, Kecamatan Kembayan, Kabupaten Sanggau, dengan luas areal sekitar 20 hektar. Terdapat empat jenis lahan berdasarkan kepemilikan dan pengelolaan petani. Metode survey dan pengambilan contoh tanah menggunakan metode sistem grid. Sampel tanah diambil pada kedalaman 0-30 cm dan 30-60 cm secara komposit untuk analisis sifat kimia tanah. Sampel tanah utuh juga diambil menggunakan ring sampler pada kedalaman 0-30 cm. Analisis tanah di laboratorium meliputi pengukuran pH tanah, kandungan C-organik, N-total, P-tersedia, K-dd, kapasitas tukar kation tanah, kejenuhan basa tanah dan bobot isi. Lahan kelapa sawit di tanah Ultisol pada semua lokasi memiliki karakteristik kimia tanah yang serupa, dengan kecenderungan memiliki kadar nutrisi yang rendah. Hal ini terbukti melalui analisis sampel tanah yang menunjukkan rendahnya kandungan unsur hara esensial. Selain itu, praktik manajemen dan pengelolaan lahan yang terbatas, seperti pemupukan yang tidak seimbang, berdampak pada sifat kimia tanah dan ketersediaan nutrisi dalam tanah. Kata kunci: Tanah Ultisol, Sifat Kimia, Kelapa Sawit